Validation of the World Health Organization’s Disability Assessment Schedule 2.0 for children with mental disorders in specialized health-care services - Díaz-Castro, Lina; Arroyo-Belmonte, Miriam; Suárez-Brito, Paloma; Márquez-Caraveo, María Elena; Garcia-Andrade, Consuelo (Frontiers in Psychiatry, 2024)
IntroductionMental disorders are highly prevalent among children, yet access to timely and effective treatment remains limited. Untreated or poorly managed mental disorders in children are associated with significant functional deterioration and long-term consequences. The validation of reliable assessment tools is crucial for identifying functional impairments and guiding interventions in this population. This study aimed to assess the utility and psychometric properties of the World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0) in evaluating functional impairment among children and adolescents receiving specialized mental health care in Mexican psychiatric hospitals.MethodA cross-sectional analytical study was conducted from January 2018 to February 2020 in two psychiatric public hospitals in Mexico. The Spanish version of the WHODAS 2.0 was adapted for the pediatric population, and its psychometric properties were evaluated among 390 children and adolescents receiving psychiatric care. Data were analyzed using descriptive statistics, exploratory and confirmatory factor analyses, and tests of internal consistency and validity.ResultsThe WHODAS 2.0 demonstrated high internal consistency (α = .92) and convergent validity, with significant correlations observed between WHODAS scores and clinical variables. Exploratory factor analysis revealed a six-dimensional structure, with gender-specific differences identified in functional impairment patterns.DiscussionThe study provides robust evidence supporting the utility and psychometric properties of the WHODAS 2.0 for assessing functional impairment in children and adolescents with mental disorders in Mexican psychiatric hospitals. These findings have implications for clinical practice, policy-making, and future research aimed at improving outcomes for this vulnerable population.